Attitude, subjective norm an perceived behavior control on whistleblowing intention in avoiding fraud - Amelia Oktrivina (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2022)
This study analyzes how attitude, subjective norms, and perceived behavior control affect whistleblowing intention. This study took a sample using a questionnaire at the Badan Pemeriksa Keuangan (BPK). A purposive sampling method has been applied to determine 30 employees at Badan Pemeriksa Keuangan (BPK) was obtained based on predetermined criteria. The method of analysis in this study uses descriptive statistical analysis. The tool for this research uses SPSS. The results of this study indicate that attitude, subjective norms, and perceived behavior control affect whistleblowing intention.